Analysis of Tobacco Consumption Behavior in Adolescents at Kediri Regency - Ema Mayasari; Yeni Muslicha Dwi Rahayu; Amarin Yudhana (Universitas STRADA Indonesia, 2023)
Background: The prevalence of adolescent smokers in Indonesia is very worrying, with an estimated number of 70 million children in Indonesia and making Indonesia the third country with the highest number of smokers in Asia. The tendency of adolescents who want to try smoking causes health problems. Purpose: The purpose of this research is to know the description of smoking habits among adolescents in Kediri Regency. Method: This research is a survey research with a population of all adolescent groups in Kediri Regency. Samples were taken purposively by 300 respondents. The data collection method in this study used a questionnaire. This study uses a quantitative descriptive technique by describing several variables including pocket money, the role of health workers, information on the dangers of smoking, cigarette advertisements, knowledge, attitudes, smoking status. Results: The majority of adolescent smokers in Kediri Regency are male with an age range between 14-16 years with junior high school education. The average number of cigarettes consumed is between 1 to 4 cigarettes, spending an average of Rp. 300,000 per month for the type of cigarette consumed, the majority of which are white cigarettes. The first time they got to know cigarettes at the age of 14 to 15 years was 123 people (79%). They know cigarettes through exposure to internet media. Conclusion: The Adolescents have various reasons behind their smoking behavior. They tend to have great curiosity. The habit of smoking for students begins because they are consumed by advertisements and persuaded by friends.